Autoriser pour interdire. La fabrique des savoirs sur les molécules et leurs risques dans le règlement européen REACH - Henri Boullier (Revue de la Régulation, 2016)
How can toxic chemicals be regulated with limited and incomplete data on their properties? Since the Toxic Substances Control Act was adopted in the United States in 1976, information asymmetries and the multiplication of specific applications for chemicals had apparently made their control almost impossible. With the authorisation procedure, the european regulation on the registration, evaluation and authorisation of chemicals (REACH), adopted in 2006, introduces a novel way of controlling the most toxic chemicals. The dissertation shows how such a procedure sets new standards in regulatory control in spite of information asymmetries between regulators and firms. The authorisation procedure renders public authorities able to ban “substances” based on their hazards while some “uses” of these chemicals can be maintained on the market on the basis of invidual applications submitted by firms. In order to have such applications accepted, firms provide public authorities with new toxicological and exposure data for very specific uses, and socio-economic analyses that had never been produced before. Although REACH is based on existing regulatory tools, the authorisation procedure profoundly modifies the relationship between regulators and firms, modifies the objects of regulation and transforms the ways in which regulatory knowledge for decision making is produced.